Assessment Methodology of Interior Aircraft Noise Influence on Pilot Performance and Temporary Threshold Shift - Ivošević, Jurica; Bucak, Tino; Sumpor, Davor (Promet - Traffic&Transportation, 2016)
Previous studies have shown that the impact of interior aircraft noise on pilot performance was not unambiguous, neither there was any unanimous methodology used for measuring it. Furthermore, the cumulative character of noise was never taken into account. This research proposes a methodology that aims to determine the impact of accumulated general aviation aircraft interior noise on pilot performance in laboratory conditions. The assessment of the aircraft interior noise influence on Temporary Threshold Shift is integrated as well, enabling extended research of all aspects of the physiological noise impact on pilots. Methodology defines measurable noise and pilot performance parameters in general aviation, equipment requirements, necessary laboratory conditions and subject selection criteria. The analysis of the deviation from the specified flight parameters along with Temporary Threshold Shift values at different accumulated noise doses is carried out. Data is analyzed using descriptive statistics, visualization methods and linear mixed effects models with False Discovery Rate as the method for correction for multiple testing which allows the determination of the potential population effect.